Upper and lower bounds for the bit error rate for multiple photodiode balanced detectors in SAC OCDMA systems - Alhassan, A.M. (IEEE Computer Society, 2014)
Intensity noise (IN) or phase induced intensity noise (PIIN) is the key limiting factor of the performance in spectral amplitude coding optical code division multiple access (SAC OCDMA) systems. The PIIN can be mitigated in SAC OCDMA by splitting the signals and detecting each signal by a different photodiode if the independence between the split signals can be achieved. In this paper, we derive the upper and lower bounds for the bit error rate (BER) for a system that implements multiple photodiode structured balanced detectors. Additionally, a simulation using Optisystem is conducted to compare the performance of the conventional balanced detector and an ideal multi photodiode balanced detector. Â© 2014 IEEE.